2019
DOI: 10.32828/mdj.v11i1.872
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the amount of apically extruded debris using different root canal instrumentation systems

Abstract: The purpose of this study was to evaluate the amount of apically extruded debrisusing 5 types of nickel–titanium endodontic instruments (Hand ProTaper, RotaryProTaper, Rotary Mtwo, RECIPROC and WaveOne). Seventy-five freshly extractedmandibular premolar teeth were used in this study. All teeth were shortened to alength of 14mm. The specimens were randomly divided into five groups (each groupcontaining 15 samples) according to the type of instrumentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Several factors contribute to the immunological fitness of an individual. The host exists in a symbiotic relationship with the oral microbiome to maintain homeostasis [19][20][21]. explaining the fluctuation of some chemokines levels during disease progression in favor of elevation of others.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors contribute to the immunological fitness of an individual. The host exists in a symbiotic relationship with the oral microbiome to maintain homeostasis [19][20][21]. explaining the fluctuation of some chemokines levels during disease progression in favor of elevation of others.…”
Section: Discussionmentioning
confidence: 99%
“…Then the rubber stopper with the root was removed from the collecting vial, and the root apex was washed off with 1 ml of deionized water using a disposable plastic syringe [ 25 ]. The collecting vials were placed in a dry heat oven at 110°C for 3 hr to ensure the dryness of any remaining solution [ 26 ]. Then the vials were transported from the oven using Cheatle Forceps and kept in a dry sealed desiccator that contained CaSO 4 crystals for 24 hr before weighing.…”
Section: Methodsmentioning
confidence: 99%
“…However, the self-adjusting file system resulted in the least amount of debris extrusion among them. Likewise, Hussein et al [11] evaluated the quantity of apical extrusion of debris using Rotary ProTaper, Rotary M two, Reciproc and WaveOne. The results showed that these instruments resulted in apical extrusion however, WaveOne produced the highest amount of debris extrusion.…”
Section: Introductionmentioning
confidence: 99%